Simulation study of packaging with ergonomic considerations - Ramanathan Velmurugan (2008)
In the modem manufacturing era, every industry is moving from mass production to lean manufacturing and flexible manufacturing systems. The companies are going global, giving importance to design, manufacturing and other functions, which directly support the product. Most of the industries are not considering packaging operation as an integral part of their manufacturing system. Packaging operation is not adding value to the product other than marketing purpose, because the product is already available. This project deals with applying Ergonomics to improve the performance of the packaging system in terms of cost reduction, good quality, and better work practices, which in turn improves the efficiency of the system and effectiveness of the work force. Applying Ergonomic solutions in packaging and the benefits of Ergonomic approach in packaging in terms of work place design; task design and better work practices are explained with the help of case study. The improvement in resource utilization is evaluated using simulation.